Expert opinion and patients' in-depth interviews on the impact of pulmonary complications in systemic sclerosis. (10th November 2021) - Caminati, Antonella; Vigone, Barbara; Cozzaglio, Sergio; De Nigris, Paola; Galetti, Ilaria; Nunzio, Sara di; Verzeletti, Viviana; Cighetti, Jennifer; Garbagnati, Carla; Paleari, Laura; Tabaglio, Erminio; Pirri, Salvatore
Abstract: Objective: To qualitatively explore the perceptions and opinions of experts dealing with systemic sclerosis (SSc) and patients with SSc on the impact of the disease and pulmonary complications on economic status, psycho-social wellbeing and the diagnostic and therapeutic journey, and to identify which strategies/interventions may be useful to address patients' and their family's needs. Methods: An expert meeting was conducted using the NGT to discuss the consequences of pulmonary complications on the Italian SSc community. The direct experience of five patients with SSc and pulmonary complications was described through in-depth interviews conducted by psychologists. Results: The experts' meeting and patients' in-depth interviews underline the complexity of SSc and the consequences of pulmonary involvement on patients' and caregivers' health-related quality of life, working ability, psychological wellbeing and social interactions. Panellists suggest that improved communication between physicians, associations and institutions could help protect the working status of patients with SSc. Granting patients disability benefits, providing access to part-time jobs and productivity-focused training could also help decrease the economic burden of the disease. A multidisciplinary approach is recommended to reduce treatment burden, together with the implementation of standard diagnostic and therapeutic paths and increased use of telemedicine via platforms that ensure secure health data sharing. Both patients and caregivers may benefit from psychological support. Conclusion: SSc and pulmonary fibrosis have profound consequences on patients' and caregivers' health-related quality of life, working ability, psychological wellbeing and social interactions. Some activities may help patients and families deal with these aspects of the disease.